Genetic Analyses of Generation Means For A Cross Between Two Local Breeds Of Chickens: DjDj- Comparisons Between F3 and Backcrosses For Egg Production Traits (Global Journal of Science Frontier Research, 2013)
Comparisons between F3 and Backcross combinations derived from Gimmizah x Bandarah cross were used to estimate additive and dominance effects and the average level of dominance, which control the inheritance of egg production traits. Genetic variance components were estimated using Designs ІІ and Ш. Both analysis determined that large positive additive genetic variations were found for age at sexual maturity 20.4, egg number at the first 90 d. of production 149.8 and egg number at 52 weeks of age 848.7 in backcross generations compared with the same traits in F3 generation (-52.0, 14.8 and 9.9), respectively. On the other hand small positive additive genetic variances were found for body weight at maturity (0.0144) and egg weight at maturity (0.281) in backcross generations, the corresponding values in F3 generation were -0.018 and -9.87, respectively. These results indicate that the parents Gimmizah and Bandarah contain a high proportion of additive genes for these traits, which accumulated in backcrosses. Furthermore, the F3 generation yielded higher positive dominance variance components for age at sexual maturity 287.7 and egg weight at maturity 48.6 than the corresponding variances in backcrosses 8.3 and 8.1, respectively.
Keywords: bandarah gimmizah maturity yielded